Abu Dhabi's vision 2030 an ongoing journey of economic development - Low, Linda (World Scientific Pub., 2012)
This book aims to tell the Abu Dhabi story in economic development, from its past dominance in oil to its economic vision for the future. More than being an exemplar of industrial restructuring and diversification from a resource-based to a 21st century knowledge-based economy and society, Abu Dhabi emphasises its cultural legacy and tradition as an environmental advocate for green and sustainable pathways. It has as many challenges as creative responses to show that its success is not by wealth alone. This case study unveils Abu Dhabi in particular and the rest of Arabic and GCC economic development.